Occurrence of Equatorial Plasma Bubbles during Intense Magnetic Storms - Chao-Song Huang (International Journal of Geophysics)
An important issue in low-latitude ionospheric space weather is how magnetic storms affect the generation of equatorial plasma bubbles. In this study, we present the measurements of the ion density and velocity in the evening equatorial ionosphere by the Defense Meteorological Satellite Program (DMSP) satellites during 22 intense magnetic storms. The DMSP measurements show that deep ion density depletions (plasma bubbles) are generated after the interplanetary magnetic field (IMF) turns southward. The time delay between the IMF southward turning and the first DMSP detection of plasma depletions decreases with the minimum value of the IMF Bz, the maximum value of the interplanetary electric field (IEF) Ey, and the magnitude of the Dst index. The results of this study provide strong evidence that penetration electric field associated with southward IMF during the main phase of magnetic storms increases the generation of equatorial plasma bubbles in the evening sector.